Numb Chin Syndrome as First Symptom of Diffuse Large B-Cell Lymphoma. (15th December 2014) - Carbone, Mario; Della Ferrera, Francesco; Carbone, Lucio; Gatti, Gaia; Carrozzo, Marco
Abstract : Numb chin syndrome is a rare sensory neuropathy of the mental nerve characterized by numbness, hypoesthesia, paraesthesia, and very rarely pain. Dental causes, especially iatrogenic ones, maxillofacial trauma, or malignant neoplasm are etiologic factors for this rare syndrome. Many malignant and metastatic neoplasms are causing this syndrome, like primary osteosarcoma, squamous cell carcinoma, and mandibular metastasis of primary carcinoma of breast, lung, thyroid, kidney, prostate, and nasopharynx. Haematological malignancies like acute lymphocytic leukaemia, Hodgkin and non-Hodgkin lymphoma, and myeloma can cause this neuropathy. The authors report a case of a 71-year-old woman in which the numb chin syndrome was the first symptom of the diffuse large B-cell lymphoma, which caused infiltration and reabsorption of the alveolar ridge and lower mandibular cortex. A biopsy of the mass was performed on fragments of tissue collected from the mandibular periosteum, medullary and cortical mandibular bone, and inferior alveolar nerve.